An Anthocyanin-Related Glutathione S-Transferase, MrGST1, Plays an Essential Role in Fruit Coloration in Chinese Bayberry (Morella rubra) - Xue, Lei; Huang, Xiaorong; Zhang, Zehuang; Lin, Qihua; Zhong, Qiuzhen; Zhao, Yun; Gao, Zhongshan; Xu, Changjie (Frontiers in Plant Science, 2022)
Chinese bayberry (Morella rubra) is a fruit tree economically important in China and accumulates abundant amounts of anthocyanins in fruit as it ripens. Owing to the fact that all anthocyanin containing fruit tissues in Chinese bayberry are edible and anthocyanins can provide various health benefits in human body, the mechanisms underpinning anthocyanin accumulation in this fruit are worthy of investigation. It has been known that in plants anthocyanins are synthesized in the cytoplasmic surface of the endoplasmic reticulum and subsequently transported into the vacuole for storage, and glutathione S-transferases (GSTs) have been verified to be involved in this process. But the characterization and functionalization of the GST counterpart in Chinese bayberry is not available. The GST anthocyanin transporter MrGST1 was discovered to be related with anthocyanin accumulation in fruit from distinct developmental stages of 'Biqi', a staple cultivar that accumulates over 1 mg/g anthocyanins in ripe fruit. The expression of MrGST1 was well associated with anthocyanin accumulation either in fruit collected at six developmental stages or in ripe fruit from 12 cultivars. MrGST1 was found to be responsible for the transport of anthocyanins but not proanthocyanidins when the Arabidopsis tt19 mutant was functionally complemented. Transient ectopic expression of MrGST1 in combination with MrMYB1.1 and MrbHLH1 dramatically boosted pigmentation in Nicotiana tabacum leaves in contrast to MrMYB1.1 and MrbHLH1. The promoter of MrGST1 comprised eight MYB binding sites (MBSs) according to cis-element analysis. Data from yeast one-hybrid assay and dual-luciferase tests demonstrated that MrMYB1.1 exerted considerable transactivation effect on the MrGST1 promoter by recognizing the MBS4, the fourth MBS from the ATG start site. Our results together provided molecular evidence for the contribution of MrGST1 in regulating anthocyanin accumulation in Chinese bayberry fruit.